Tecnologia e sociedade : teste de desempenho escolar em ciências - Lima, Rafael Pina (2016)
This study aims to describe the paths traversed during the process of construction, development and validation of a test of school performance in science. Process that has led us to reflect and rethink questions related to the evaluation process and, mainly, to assess. Assess student learning and their interest in learning science seems challenging, but in a way, when trying to identify approaches and distances in relation to the reference are sought knowledge indicative of how's science education and what is the interest of students in learning science. In Brazil, recent studies have revealed that few States never imposed their own evaluation systems, participating in national systems only as the basic education evaluation system (SAEB) and the national high school Exam (ENEM). In this sense, this dissertation aimed to the development of a test of school performance in science for students graduating from elementary school of the State of Sergipe with specificity in the main theme "technology and society". This technology, unlike traditional assessments, aims to assess students Sergipe from public the closeness and distance of student speech in relation to scientific knowledge on topics of this main theme. The elaboration of the issues was guided by an array of reference, document constructed from the analysis of three official documents, national curriculum Parameters (PCN) (BRAZIL, 1998), Curricular Reference of State schools of Sergipe (SERGIPE, 2013) and textbook approved in National Textbook Program (PNLD) 2014. The results of the application of the test to a sample of students Sergipe proved interesting, with varying performance of approximation and distancing. With these analyses, it can concluded that it is possible to assess the performance of students even changing the nature of the issues. However, future research will seek ways to be able to compare the results of this test with traditional tests in order to evaluate possible differences of performance testing.